Feasibility of Measuring GABA Levels in the Upper Brainstem in Healthy Volunteers Using Edited MRS - Song, Yulu; Gong, Tao; Edden, Richard A. E.; Wang, Guangbin (Frontiers in Psychiatry, 2020)
Purpose: To assess the feasibility of small-voxel MEGA-PRESS in detecting gamma-aminobutyric acid (GABA) levels of the upper brainstem in healthy volunteers. Materials and Methods: Forty-two healthy volunteers, aged between 20 and 76 years were enrolled in this study, and underwent a 3.0T MRI scan using an eight-channel phased-array head coil. The MEGA-PRESS sequence was used to edit GABA signal from a 10x25x30 mm3 voxel in the upper brain stem. The detected signal includes contributions from macromolecules (MM) and homocarnosine and is therefore referred to as GABA+. All the data were processed using Gannet. Results: Thirty-four cases were successful in measuring GABA in the upper brainstem and 8 cases failed (based on poor modeling of spectra). The GABA+ levels were 2.66±0.75 i .u. in the upper brainstem of healthy volunteers, ranging from 1.50 to 4.40 i .u.. The normalized fitting residual (FitErr in Gannet) was 12.1±2.8 %, ranging from 7.4% to 19.1%; it was below 15.5% in 30 cases (71%). Conclusions: It is possible to measure GABA levels in the upper brainstem using MEGA-PRESS with a relatively small ROI, with a moderate between-subject variance of under 30%.